Clonal Propagation of schleichera Oleosa by Cleft Grafting - Sinha, Animesh (Indian Forester, 2012)
Cleft grafting was attempted in Schleichera oleosa (Lour.) Oken (Syn. S. trijuga Willd). The effect of covering of scion after graft union, grafting season and tree age were evaluated for the success of graft union. Maximum success (56.7%) was recorded when all leaves were removed from scion and incense stick cover was completely sealed to prevent desiccation of scion. June monthwas found to be best time for grafting of this species in eastern part of India. However, no grafting success was observed when scion was taken from trees having more than 40 years of age.